Pengembangan Media Pembelajaran Berbasis Game Educaplay untuk Meningkatkan Keaktifan Siswa pada Mata Pelajaran SKI - Saiful Anwar; Jasiah Jasiah (Jurnal Budi Pekerti Agama Islam, 2025)
Education in the digital era faces challenges in creating an interesting and effective learning process, especially in the subject of Islamic Cultural History (SKI) which is often considered monotonous. This study aims to develop Educaplay game-based learning media to increase student activeness in learning SKI. This research uses a Research and Development approach using the Dick and Carey model with a research sample of seventh grade students of MTS Muslimat NU Palangka Raya. The results showed that the use of Educaplay game media can increase students' activeness, as well as improve their understanding of SKI material, despite challenges in technology adaptation and understanding abstract concepts. This research shows the importance of technological innovation in Islamic learning, especially in creating relevant learning experiences in the digital era.